2023
DOI: 10.1093/neuonc/noad136
|View full text |Cite
|
Sign up to set email alerts
|

A closer look at the role of iron in glioblastoma

Abstract: Glioblastoma is among the deadliest malignancies facing modern oncology. While our understanding of certain aspects of glioblastoma biology has significantly increased over the last decade, other aspects, such as the role of bioactive metals in glioblastoma progression, have remain understudied. Iron is the most abundant transition metal found within the earth’s crust and plays an intricate role in human physiology owing to its ability to participate in oxidation-reduction reactions. The importance of iron hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 126 publications
0
2
0
Order By: Relevance
“…Some studies have found no association between anemia and survival 39 , while others have found a negative association of anemia with survival among glioblastoma patients 40 43 . These studies are summarized in Table 3 and reviewed in greater detail elsewhere 44 . Of note, these studies have been limited to single institutions and smaller patient cohorts with insufficient size to study sex as a biological variable.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found no association between anemia and survival 39 , while others have found a negative association of anemia with survival among glioblastoma patients 40 43 . These studies are summarized in Table 3 and reviewed in greater detail elsewhere 44 . Of note, these studies have been limited to single institutions and smaller patient cohorts with insufficient size to study sex as a biological variable.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increased interest in the use of small paramagnetic iron oxide nanoparticles for tumor imaging, understanding the impact of iron on the behavior of glioblastomas is critical. [13][14][15] 2 | MATERIALS AND METHODS 2.1 | Cell culture T98G (ATCC, Catalog #: CRL-1690) and LN229 (ATCC, Catalog #: CRL-2611) authenticated human glioblastoma cell lines were purchased from the American Type Culture Collection (ATCC). T98G cells were cultured in RPMI 1640 supplemented with GlutaMAX™ (ThermoFisher Scientific, Catalog #: 61870127), 10% fetal bovine serum (GeminiBio, Catalog#: 100-106), and 1% Penicillin-Streptomycin (ThermoFisher Scientific, Catalog #: 15140-122).…”
Section: Introductionmentioning
confidence: 99%